MENINGKATKAN SIKAP TOLERANSI PADA DOMAIN AFEKTIF, KOGINITIF DAN PERILAKU SISWA DALAM INTEGRASI PENDIDIKAN AGAMA KRISTEN DAN BUDI PEKERTI MELALUI PENERAPAN METODE FILMED ROLE-PLAY [INCREASING TOLERANCE IN STUDENTS' AFFECTIVE, COGNITIVE, AND BEHAVIOUR DOMAINS THROUGH THE INTEGRATION OF CHRISTIANITY AND MORAL STUDIES USING THE FILMED ROLE-PLAY METHOD] - Stephanie Stephanie (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2021)
Indonesia is a religion based country. Religion studies should be positioned as school’s curriculum priority, both in public and private school. Integrated Christianity and moral studies might be the solution of conflicts within family, school, community, both national and international societies. One of many values that urgently needs to be promoted is an attitude of tolerance in facing our multicultural society. School as an educational institution has an important role in teaching tolerance skill to students as early age. One of the challenges is finding the right method to deliver the abstract concepts to children who are in the stage of pre-operational concrete. This research has done an introductionary study towards the bullying case that happened earlier in the researchers workplace 4th and 5th graders within 4 months. Therefore, this research address the urgency of an integrated curriculum of Christianity studies with moral studies practices, specifically on multicultural values through experiential learning with filmed role-play. Research was conducted in XYZ School for primary 3, 4 and 5. This instructional strategy resulted in increase of attitude of tolerance both in cognitive and behavior domain, but has no increase in the affective domain. All respondents agree by implementing filmed role-play has contributed to their deeper understanding towards the concept of tolerance.